2012
DOI: 10.5293/ijfms.2012.5.4.168
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on Aerodynamic Performance of a Centrifugal Fan with Splitter Blades

Abstract: This paper presents a numerical investigation on the aerodynamic performance according to the application of splitter blades in an impeller of a centrifugal fan used for a refuse collection system. Numerical analysis of a centrifugal fan was carried out by solving three-dimensional Reynolds-averaged Navier-Stokes equations with the shear stress transport turbulence model. A validation of numerical results was conducted by comparison with experimental data for the pressure and efficiency. From analyses of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…As a result, the accuracy of the numerical model was verified. Kim et al [6] presented a numerical analysis model for the splitter-type centrifugal fan and confirmed that the splitter blade improved the fan's overall performance. Chunxi et al [7] conducted a study on the performance of centrifugal fans with 5% and 10% increases in the impeller size by extending the tip of the blade without changing the size of the volute.…”
Section: Introductionmentioning
confidence: 90%
“…As a result, the accuracy of the numerical model was verified. Kim et al [6] presented a numerical analysis model for the splitter-type centrifugal fan and confirmed that the splitter blade improved the fan's overall performance. Chunxi et al [7] conducted a study on the performance of centrifugal fans with 5% and 10% increases in the impeller size by extending the tip of the blade without changing the size of the volute.…”
Section: Introductionmentioning
confidence: 90%
“…These contributions are made on the influence of different structural factors on the impeller performance. Kim et al 16 investigated the effect of blade numbers and splitter blades. Simulations and experiments illustrated a great regression of fluid performance caused by different clearance between casing and blades.…”
Section: Introductionmentioning
confidence: 99%
“…Hariharan et al [11] found that an appropriate ratio between the impeller exit width and volute width generates a more uniform flow distribution which reduces the structural load on the impeller. Kim et al [12] presented a numerical investigation on the aerodynamic performance according to the application of splitter blades in an impeller of a centrifugal fan used for a refuse collection system. The results show that splitter blades in a centrifugal fan lead to a significant improvement in the overall fan performance.…”
Section: Introductionmentioning
confidence: 99%